The Many Roles of Macrophages in Skeletal Muscle Injury and Repair - Wang, Xingyu; Zhou, Lan (Frontiers in Cell and Developmental Biology, 2022)
Skeletal muscle is essential to physical activity and energy metabolism. Maintaining intact functions of skeletal muscle is crucial to health and wellbeing. Evolutionarily, skeletal muscle has developed a remarkable capacity to maintain homeostasis and to regenerate after injury, which indispensably relies on the resident muscle stem cells, satellite cells. Satellite cells are largely quiescent in the homeostatic steady state. They are activated in response to muscle injury. Activated satellite cells proliferate and differentiate into myoblasts. Myoblasts fuse to form myotubes which further grow and differentiate into mature myofibers. This process is tightly regulated by muscle microenvironment that consists of multiple cellular and molecular components, including macrophages. Present in both homeostatic and injured muscles, macrophages contain heterogeneous functional subtypes that play diverse roles in maintaining homeostasis and promoting injury repair. The spatial-temporal presence of different functional subtypes of macrophages and their interactions with myogenic cells are vital to the proper regeneration of skeletal muscle after injury. However, this well-coordinated process is often disrupted in a chronic muscle disease, such as muscular dystrophy, leading to asynchronous activation and differentiation of satellite cells and aberrant muscle regeneration. Understanding the precise cellular and molecular processes regulating interactions between macrophages and myogenic cells is critical to the development of therapeutic manipulation of macrophages to promote injury repair. Here, we review the current knowledge of the many roles played by macrophages in the regulation of myogenic cells in homeostatic, regenerating, and dystrophic skeletal muscles.